VD_FINDINFO ACH 117/24 - 128/2025 vom 18. August 2023 - VD Tribunal cantonal (2023)
CHÔMAGE, REFUS D'UN TRAVAIL CONVENABLE, SANCTION ADMINISTRATIVE, ADMISSION PARTIELLE | 17 al. 3 LACI, 30 al. 1 let. d LACI, 45 al. 3 OACI, 45 al. 4 OACI